Efeitos do laser e da terapia fotodinâmica no tratamento periodontal mecânico em ratas ovariectomizadas e sob influência sistêmica de nicotina: estudo histomorfométrico e imunoistoquímico - Gualberto Júnior, Erivan Clementino [UNESP] (2013)
This study evaluated histomorphometrically, immunohistochemically and by polymerase chain reaction via real-time reverse transcriptase (qRT-PCR) the effects of Laser Therapy in Low Intensity (LLLT) and antimicrobial Photodynamic Therapy (aPDT) adjuncts to mechanical treatment of periodontitis experimental (PE) in rats with estrogen deficiency and under the influence of systemic nicotine. It was used 360 rats divided into 4 groups: Group SH-veh: sham treated with saline (vehicle); Group SH-nic: sham treated with nicotine; Group OVX-veh: ovariectomized treated with saline (vehicle) and Group OVX-nic: ovariectomized treated with nicotine. Nicotine was administered to groups SH-nic and OVX-nic 30 days before the induction of PE. The animals in Groups OVX-veh and OVX-nic underwent ovariectomy (OVX) bilaterally 21 days before PE performed by adaptation of cotton thread around the first molars right and left. After 7 days, the ligature was removed and the animals divided according to the following local treatments performed in the right and left molars: RAR - Scaling and root planing and irrigation with saline; LLLT - RAR and irrigation with saline associated with LLLT; aPDT - irrigation with toluidine blue O (TBO) and after 1 minute irradiation with LLLT. Ten animals were euthanized of each group at 7, 15 and 30 days after treatment site. Bone loss (BL) in the furcation was evaluated by histomorphometric and immunohistochemical analyzes. The gene expression of TNF-α, IL-1β and IL-6 were measured by qRT-PCR. Data were subjected to statistical analysis (α = 5%). The animals of the OVX-nic group showed higher BL group compared with SH-vei (p <0,05). Local treatment with aPDT showed BL reduced, decreased expression of RANKL and the number of TRAP-positive cells and increased the expression of OPG and the number...